Prostitution and beyond: an analysis of sex work in India - Sahni, Rohini (Sage Publ., 2008)
section 1. Through the looking glass : sex work, feminism and theoretical debates -- section 2. Through the kaleidoscope of time : changing forms and emerging realities -- section 3. At the interface : economic, social, legal and health perspectives -- section 4. Looking in the mirror of culture : representations of prostitution